JAMINAN ILAHI DAN KETAHANAN UMAT DALAM PENDIDIKAN ISLAM : EKSPLORASI KRITIS TERHADAP NARASI HADIST QUDSI - Nurhalim; Irawan, Robi; Muhammad Akmansyah (As-Sulthan Journal of Education, 2025)
Muslim concerning divine assurance (Divine Assurance) for the endurance of the Muslim ummah. Employing a qualitative library research method with a hermeneutic approach, this research analyzes classical commentaries and contemporary interpretations to explore the relevance of the hadith to Islamic education and community resilience. The findings reveal that divine assurance emphasizes collective protection rather than individual immunity, signifying that the strength of the ummah lies in unity, moral integrity, and spiritual awareness. Internal division, moral degradation, and loss of faith are identified as dominant factors that threaten Islamic civilization. The study also finds that the hadith provides a pedagogical foundation for strengthening Islamic brotherhood., Islamic ethics, and character formation through education based on faith and morality. The conclusion asserts that Islamic education must serve as an instrument of ummah resilience, integrating faith, knowledge, and ethics to produce the man of adab humans of virtue, intellect, and social responsibility capable of preserving unity and reviving Islamic civilization amid modern global challenges.